2020
DOI: 10.3390/su13010158
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Assessment of Carbon Footprint of Bike-Share and Bus Systems in Campus Transit

Abstract: Low-carbon transport system is desired for sustainable cities. The study aims to compare carbon footprint of two transportation modes in campus transit, bus and bike-share systems, using life-cycle assessment (LCA). A case study was conducted for the four-campus (College Ave, Cook/Douglass, Busch, Livingston) transit system at Rutgers University (New Brunswick, NJ). The life-cycle of two systems were disaggregated into four stages, namely, raw material acquisition and manufacture, transportation, operation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…During the use phase, most of the emissions came from the rebalancing and maintenance strategy (Bonilla-Alicea et al, 2020 ; Luo et al, 2019 ; Sun & Ertz, 2021b ; Tao & Zhou, 2021 ; Wang et al, 2021 ). Hollingsworth et al ( 2019 ) argue that sharing organisations can reduce climate impacts by using fuel-efficient vehicles for rebalancing, optimising routes (and thereby reducing driving distances), and only collecting vehicles that need to be recharged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the use phase, most of the emissions came from the rebalancing and maintenance strategy (Bonilla-Alicea et al, 2020 ; Luo et al, 2019 ; Sun & Ertz, 2021b ; Tao & Zhou, 2021 ; Wang et al, 2021 ). Hollingsworth et al ( 2019 ) argue that sharing organisations can reduce climate impacts by using fuel-efficient vehicles for rebalancing, optimising routes (and thereby reducing driving distances), and only collecting vehicles that need to be recharged.…”
Section: Resultsmentioning
confidence: 99%
“…For fuel depletion, impacts occurring during the production phase account for 60%–78% of total impacts, while those in the use phase account for 40%–70%. The EoL phase has limited impacts (de Bortoli, 2021 ; Moreau et al, 2020 ; Wang et al, 2021 ; Wortmann et al, 2021 ). Fuel depletion was driven by the need for additional infrastructure (such as the share bike docks) and influenced by the service life and utilisation rate of the vehicles in the shared system, as well as by the rebalancing strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Sishen Wang et al [48] Bruce Appleyard et al [28] Stefan Zimmermann et al [49] Suresh Jain et al [50] Lesser studies probed the realization of campus carbon neutrality from the perspective of campus transportation, social participation and system evaluation.…”
Section: Zero Carbon Campus Systematic Design Dimensionsmentioning
confidence: 99%
“…Therefore, each bike used at least 686 days to achieve a net positive reduction in emissions. Wang Sishen et al compared the carbon footprint of two transportation modes in campus transit-bus and bike-share systems-using a life-cycle assessment (LCA) [31]. The results showed that the majority of CO 2 emissions and energy consumption comes from the raw material stage of the bike-share system and the operation stage of the campus bus system.…”
Section: Literature Reviewmentioning
confidence: 99%